2020
DOI: 10.22603/ssrr.2019-0100
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Peripheral Nerve Sheath Tumor of the Cervical Spine Treated with Surgical Resection Followed by X-ray Radiotherapy or Carbon Ion Radiotherapy: A Report of Three Cases

Abstract: This case report was approved by the institutional review boards at Gunma University and the institutional review board overseeing the central data management center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…MPNSTs are highly aggressive and locally invasive rare malignancies with an incidence of 0.0001% in the general population and 3%–5% in patients with neurofibromatosis type 1 (NF1) ( 2 ). Lesions are most frequently found on the trunk, extremities, and head and neck.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MPNSTs are highly aggressive and locally invasive rare malignancies with an incidence of 0.0001% in the general population and 3%–5% in patients with neurofibromatosis type 1 (NF1) ( 2 ). Lesions are most frequently found on the trunk, extremities, and head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…The best adjuvant treatment remains poorly defined due to the lack of prospective trials. Previous literature suggests that adjuvant radiotherapy after surgery could be an effective treatment for patients, especially in lesions larger than 5 cm in size or with residual tumor, which is critical in the prognosis of primary spinal intradural MPNSTs ( 2 , 7 , 8 , 31 ). However, our study revealed that radiotherapy is ineffective in controlling recurrence and does not appear to affect overall survival, which may be due to the bias caused by the fact that more aggressive tumors are more likely to undergo radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report of the oncological outcome and toxicity rates of mPNST/PNST patients treated with protons using a PBS delivery paradigm. Of note, two retrospective studies and two case reports analyzing mPNSTs treated with carbon ion (C12) particles were published ( 18 20 ). Jensen et al., 2015 ( 18 ) reported on the outcome and toxicity of 11 patients with unresected or incompletely resected mPNSTs treated with C12 irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of surgical treatment is to remove the tumor, relieve nerve compression and rebuild the stability of the spine. Spinal tumor surgery usually involved long operation time, large area of soft tissue resection and long wound, and was prone to hypothermia during the operation [ 1 6 ].…”
Section: Introductionmentioning
confidence: 99%